HIRE ME WEBSITE AND MOBILE APPLICATION - Mohammad Adwan; Hamzah Fattouh (My University, 2024)
Recruitment is considered a key factor influencing the development of a competitive advantage. These days, there is a high demand for workers. The challenge of selecting qualified people from the applicant pool is getting more challenging as the market gets more competitive. Furthermore, it has become imperative to understand how to draw in the top candidates. Employers and job searchers can connect through third-party recruitment websites that offer Internet-based recruitment services (referred to as "job search websites"). Job-search websites give employers direct access to an extensive resume database, which shortens the recruiting cycle. Job searchers can upload their resumes online and hunt for jobs by evaluating a constantly growing database of openings by using job-search websites. Hier me websites can help companies and job seekers find efficient solutions while overcoming obstacles related to time and location. They can also be convenient and cost-effective. While hiring through a company or job search website is like hiring through more traditional methods in many ways, there are also some differences. Websites, for example, enable the sharing of nearly infinite company information in various formats. Another issue is that job advertising websites make it simple for potential employees to compare multiple employment offers. Then, they can select the one that most closely fits their requirements and qualifications. This project aspires to provide a website and mobile application to make it easy to find a job with little effort. For the project to able to compete with other sites, which are growing rapidly, especially with the tremendous development of artificial intelligence, it will be provided with: the presence of paid accounts for the company’s, sending a notification through the email for all registered users, filtered CV and evaluation of it. The job search website includes features: • Advanced search functionality with filters and sorting options to refine job searches. • Detailed job listing pages; displaying job descriptions, requirements, and application instructions. • Seamless integration with XAMPP database for efficient data management and retrieval. • Responsive design to ensure optimal user experience across various devices. • This project aims to provide a robust and user-friendly job search platform that effectively connects job seekers with relevant job opportunities and empowers employers to streamline their recruitment processes.